Clinical pharmacist review: A randomised controlled trial. (19th July 2015) - Briggs, Sheridan; Pearce, Robert; Dilworth, Sophie; Higgins, Isabel; Hullick, Carolyn; Attia, John
Abstract Objectives To determine if medication review by a clinical pharmacist of older patients in the ED impacted on admission to hospital and other outcomes. Methods A stratified, randomised controlled study comparing the intervention to current practice. A tertiary referral ED in New South Wales, Australia. Older people (>70 years) living at home who initially reported taking greater than five medications. Medication review by an experienced hospital pharmacist within the ED. Rate of admission, rate of readmission, length of stay and admission to an aged care facility at 4 months post presentation, and rate of general practitioner acceptance of pharmacist recommendations. Results The odds of admission decreased for those receiving the intervention (odds ratio [OR] = 0.68, 95% confidence interval [CI]: 0.53, 0.87; P = 0.002). There was no evidence that the intervention affected hospital length of stay for admitted patients (0.09 days change, 95% CI −0.08, 0.25; P = 0.31), the rate of re‐presentation (0.08% change, 95% CI −0.12, 0.28; P = 0.44) or admission to an aged care facility. The odds of admission to an aged care facility increased with the Identification of Seniors at Risk score. General practitioners adopted 49% of pharmacists' recommendations. Conclusions The presence of an experienced pharmacist in the ED reduced hospital admissions. Further study is required to determine longer term impacts of General Medical Practitioner acceptance of pharmacists' recommendations.